If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(w-2)+5=2(3w-5)
We move all terms to the left:
2(w-2)+5-(2(3w-5))=0
We multiply parentheses
2w-(2(3w-5))-4+5=0
We calculate terms in parentheses: -(2(3w-5)), so:We add all the numbers together, and all the variables
2(3w-5)
We multiply parentheses
6w-10
Back to the equation:
-(6w-10)
2w-(6w-10)+1=0
We get rid of parentheses
2w-6w+10+1=0
We add all the numbers together, and all the variables
-4w+11=0
We move all terms containing w to the left, all other terms to the right
-4w=-11
w=-11/-4
w=2+3/4
| 2·x2=18 | | 6m–21=459 | | X²-4x=60 | | 4x(x)-49=0 | | 3x+21=5-21 | | (6-5x)(4x+1)=0 | | 6x+9=3(2x+3 | | (2x+11)=(3x−24) | | 3/4x-5/8x=-1/2 | | 17x(4x-7)=72 | | 4n-27=50 | | 15v=150 | | 15|7m-28|25=3|5m+25|11 | | x+7=92 | | 2x=3x+1-1 | | 10,111.99=7,750(1+x)9 | | 1=2x+35 | | w·(w·2)=180 | | 16+6.4n=14+6.9n | | -144=12w | | 7x+5-3x=4x+5 | | x/4x-3=5x+9 | | n=-12+30 | | 5x+9=5x-6 | | 13v=9v+12 | | 200m-125m+42,975=46,125-150m | | 4(x-3)-x+15=-6x+12 | | 10-2x=66-10x | | 5(x+2)-2x-4=18 | | x+(-9)=-1 | | 5x3=35 | | 4n+20=6-3n |